2021
DOI: 10.1024/0300-9831/a000623
|View full text |Cite
|
Sign up to set email alerts
|

The alternate-day fasting diet is a more effective approach than a calorie restriction diet on weight loss and hs-CRP levels

Abstract: Abstract. Background and Objective: The aim of present study was to compare, and determine, the effects of a modified alternate-day fasting diet vs. calorie restriction on inflammatory indices and coagulation factors. Methods: This was a randomized clinical trial consisting of 80 metabolic syndrome patients, who were enrolled and randomly dichotomized into a modified alternate-day fasting diet or calorie restriction group for 4 months. We measured weight, body mass index (BMI), waist circumstance (WC), waist-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 41 publications
2
44
0
2
Order By: Relevance
“…Unfortunately, due to the limited number of studies, we were unable to conduct a comparative analysis between daily TRF and CR or a non-intervention diet. In contrast, the feeding window of the non-fasting period for weekly TRF and ADF was not addressed in the viewed RCTs ( 45 , 75 ), so it was unknown whether circadian rhythms play a role in these two patterns of IF. An irregular and inappropriate diet might lead to metabolic disorders and other adverse consequences ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, due to the limited number of studies, we were unable to conduct a comparative analysis between daily TRF and CR or a non-intervention diet. In contrast, the feeding window of the non-fasting period for weekly TRF and ADF was not addressed in the viewed RCTs ( 45 , 75 ), so it was unknown whether circadian rhythms play a role in these two patterns of IF. An irregular and inappropriate diet might lead to metabolic disorders and other adverse consequences ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to examine gut microbiota during a lifestyle weight loss intervention of DCR versus IMF as well as the largest human study to date of the gut microbiota and IMF. Studies of IMF have documented that there may be enhanced health benefits relative to DCR for many measures related to cardiometabolic health, including body composition, resting energy expenditure, insulin sensitivity and inflammation [ 68 , 69 , 70 , 71 , 72 ]. We examined whether changes in gut microbiota differed between the two intervention arms, and we did not see significant differences between DCR and IMF in terms of how the overall gut microbiota changed over time (alpha- and beta-diversity).…”
Section: Discussionmentioning
confidence: 99%
“…Parvaresh et al [ 35 ], in their study among individuals with metabolic syndrome, demonstrated that ADMF may be more effective in controlling body weight, waist circumference, systolic blood pressure and fasting plasma glucose, compared with common calorie restriction. In another study, by Razavi et al, also conducted in patients with metabolic syndrome, found that ADMF was more effective in reducing body weight, fat mass, waist circumference and waist:hip ratio compared with common calorie restriction [ 36 ]. A meta-analysis by Park et al including studies using ADM or ADMF showed that this type of intermittent fasting was effective in reducing body weight, BMI and fat mass over 6 months in overweight individuals [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an important element of the therapy is its reduction [ 12 ]. Razavi et al also reported ADMF to be more effective in reducing hs-CRP levels [ 36 ]. Aliasghari et al (4 weeks of Ramadan) [ 19 ] and Mari et al (4 weeks of Ramadan) [ 25 ] also reported statistically significant decreases in hs-CRP levels in their study.…”
Section: Discussionmentioning
confidence: 99%